Molecular Characterization of SQUAMOSA PROMOTER BINDING PROTEIN-LIKE (SPL) Gene Family in Betula luminifera - Li, Xiu-Yun; Lin, Er-Pei; Huang, Hua-Hong; Niu, Ming-Yue; Tong, Zai-Kang; Zhang, Jun-Hong (Frontiers in Plant Science, 2018)
As a major family of plant-specific transcription factors, SQUAMOSA PROMOTER BINDING PROTEIN-LIKE (SPL) genes play vital regulatory roles in plant growth, development and stress responses. In this study, 18 SPL genes were identified and cloned from Betula luminifera. Two zinc finger-like structures and a nuclear location signal (NLS) segments were existed in the SBP domains of all BlSPLs. Phylogenetic analysis showed that these genes were clustered into nine groups (group I-IX). The intron/exon structure and motif composition were highly conserved within the same group. 12 of the 18 BlSPLs were experimentally verified as the targets of miR156, and two cleavage sites were detected in these miR156-targeted BlSPL genes. Many putative cis-elements, associated with light, stresses and phytohormones response, were identified in the promoter regions of BlSPLs, suggesting that BlSPL genes are probably involved in important physiological processes and developmental events. Tissue-specific expression analysis showed that miR156-targeted BlSPLs exhibited a more differential expression pattern, while most miR156-nontargeted BlSPLs tended to be constitutively expressed, suggesting the distinct roles of miR156-targeted and nontargeted BlSPLs in development and growth of B. luminifera. Further expression analysis revealed that miR156-targeted BlSPLs were dramatically up-regulated with age, whereas mature BlmiR156 level was apparently declined with age, indicating that miR156/SPL module plays important roles in vegetative phase change of B. luminifera. Moreover, yeast two-hybrid assay indicated that several miR156-targeted and nontargeted BlSPLs could interact with two DELLA proteins (BlRGA and BlRGL), which suggests that certain BlSPLs take part in the GA regulated processes through protein interaction with DELLA proteins. All these results provide an important basis for further exploring the biological functions of BlSPLs in B. luminifera.